QoE and QoS Evaluation for Academic Portal in Private Higher Education Institution - Budiman, Edy; Wati, Masna; Indra, Dolly; Moeis, Dikwan; Jamil, Muh (2018 International Conference on Computer Engineering, Network and Intelligent Multimedia (CENIM), 2018)
ISO 9126 standard provides very important key indicators as a basis for improving the quality of academic portals. The demands of users' needs for providing good quality academic portal services for students, and the time problems available in system maintenance motivate us to evaluate the main indicators of web performance that affect the performance of academic portals. This study aims to evaluate the performance of academic portals to determine the factors that influence service quality using the ISO 9126 quality model from the characteristics of reliability, efficiency, and usability academic portals in one of the Private Higher Education. Based on the measurement results of page loading time on the academic portal, it's stated that the quality of reliability characteristics is recommended to reduce page load time, which should not exceed 3 seconds. Results of quality measurement based on recommendations from Google's Page Speed obtained values with Grade D (66%) and recommendations from Page YS-Low with Grade D (67%). The results of the quality evaluation for usability characteristics recommend 4 items that fall into the category of small problems with a low priority level of improvement, and improvements needed.